Flexibility in Accessing Legal Information Through Social Media and Its Implications for Law Enforcement - Frei Fitri Astuti; Laila Nur Jannah (CV. Pustaka Parawali, 2025)
This research analyses the flexibility of access to legal information through social media and its impact on law enforcement in Indonesia. Social media makes it easy for the public to obtain legal information quickly and widely. However, the main challenge faced is the validity of the legal information circulating, which can lead to misunderstandings and affect the law enforcement process. With data collection techniques using literature studies, this research reviews regulations such as the ITE and KIP Law and literature related to legal information accessibility. The results show that although the flexibility of access through social media increases people's legal awareness, the lack of supervision of the information disseminated can undermine the legal system. Examples of viral cases show how information virality can accelerate public attention to legal issues. However, it also creates pressure on legal authorities and therefore requires strengthening regulations, public education, and adequate supervision to optimise the flexibility of access to legal information. This research contributes to a deeper understanding of the relationship between digital technology and law enforcement, especially in the context of legal information on social media. This research also provides practical recommendations for strengthening regulations, public education, and information supervision as strategic steps in improving the quality of law enforcement in the digital era. It concludes that the flexibility of access to legal information through social media can be an excellent opportunity to increase public legal awareness but must be balanced with strong regulations, consistent education and adequate supervision to prevent the misuse of legal information.and proper supervision to avoid the misuse of information that is detrimental to the legal system.